Prenatal VPA Exposure and Changes in Sensory Processing by the Superior Colliculus - Dendrinos, Georgia; Hemelt, Marie; Keller, Asaf (Frontiers in Integrative Neuroscience, 2011)
Disorders involving dysfunctional sensory processing are characterized by an inability to filter sensory information, particularly simultaneously arriving multimodal inputs. We examined the effects of prenatal exposure to valproic acid (VPA), a teratogen linked to sensory dysfunction, on the behavior of juvenile and adult rats, and on the anatomy of the superior colliculus, a critical multisensory integration center in the brain. VPA-exposed rats showed deficits in colliculus-dependent behaviors including startle response, prepulse inhibition and nociceptive responses. Some deficits reversed with age. Stereological analyses revealed that colliculi of VPA-treated rats had significantly fewer parvalbumin-positive neurons, a subset of GABAergic cells. These results suggest that prenatal VPA treatment affects the development of the superior colliculus and leads to persistent anatomical changes evidenced by aberrant behavior in tasks that require sensory processing.